1 + 4 1 ( 2 1 + 3 1 ) + 4 2 1 ( 4 1 + 5 1 ) + 4 3 1 ( 6 1 + 7 1 ) + ⋯
If the value of the series above is equal to ln A , find A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
very good...............wosks
Once you recognize the series, it is often easier to quote the Maclaurin series expansion, instead of trying to derive it all.
Amazing solution
Problem Loading...
Note Loading...
Set Loading...
Let the sum be S .
S = 1 + 4 1 ( 2 1 + 3 1 ) + 4 2 1 ( 4 1 + 5 1 ) + 4 3 1 ( 6 1 + 7 1 ) + . . . = 2 ( 2 1 + 3 1 ˙ ( 2 1 ) 3 + 5 1 ˙ ( 2 1 ) 5 + . . . ) + ( 2 1 ˙ ( 2 1 ) 2 + 4 1 ˙ ( 2 1 ) 4 + 6 1 ˙ ( 2 1 ) 6 + . . . ) = ln ( 1 + 2 1 ) − ln ( 1 − 2 1 ) − 2 1 ( ln ( 1 + 2 1 ) + ln ( 1 − 2 1 ) ) See Note. = 2 1 ln ( 2 3 ) − 2 3 ln ( 2 1 ) = ln ( 2 3 × 2 2 ) = ln 1 2
⇒ A = 1 2
Note:
We know that for 0 ≤ x < 1 , { ln ( 1 + x ) = x − 2 1 x 2 + 3 1 x 3 − 4 1 x 4 + . . . ln ( 1 − x ) = − x − 2 1 x 2 − 3 1 x 3 − 4 1 x 4 − . . .
⇒ { ln ( 1 + x ) − ln ( 1 − x ) − ln ( 1 + x ) − ln ( 1 − x ) = 2 ( x + 3 1 x 3 + 5 1 x 3 − 7 1 x 7 + . . . ) = 2 ( 2 1 x 2 + 4 1 x 4 − 6 1 x 6 − 8 1 x 8 − . . . )